Protocol of BRICS: Brazilian multicentric pragmatic randomised trial of surgical interventions for displaced diaphyseal clavicle fracture study: MIPO versus ORIF for the treatment of displaced midshaft clavicle fractures - Rafael Fuchs Lazarini; Fabio Teruo Matsunaga; João Carlos Belloti; Marcel Jun Sugawara Tamaoki; Oreste Lemos Carrazzone; Adriano Fernando Mendes Jr.; Rodrigo Fleury Curado; Jair Moreira Dias Jr.; José Da Mota Neto; Alexandre Rosa Pagan; Pedro José Labronici; Gustavo José Labronici; et al. (BMJ Open)
Introduction Fractures of the diaphysis of the clavicle are common; however, treatment guidelines for this condition are lacking. Surgery is associated with a lower risk of non-union and better functional outcomes but a higher risk of complications. Open reduction and internal fixation with plates and screws are the most commonly performed techniques, but they are associated with paraesthesia in the areas of incisions, extensive surgical exposure and high rates of implant removal. Minimally invasive techniques for treating these fractures have a lower rate of complications. The aim of this study is to evaluate which surgical treatment option (minimally invasive osteosynthesis or open reduction and internal fixation) has better prognosis in terms of complications and reoperations.Methods and analysis The study proposed is a multicentric, pragmatic, randomised, open-label, superiority clinical trial between minimally invasive osteosynthesis and open reduction and internal fixation for surgical treatment of patients with displaced fractures of the clavicle shaft. In the proposed study, 190 individuals with displaced midshaft clavicle fractures, who require surgery as treatment, will be randomised. The assessment will occur at 2, 6, 12, 24 and 48 weeks, respectively. The primary outcome of the study will be the number of complications and reoperations. For sample size calculation, a moderate effective size between the techniques was considered in a two-tailed test, with 95% confidence and 90% power. Complications include cases of infection, hypertrophic scarring, non-union, refracture, implant failure, hypoesthesia, skin irritation and shoulder pain. Reoperations are defined as the number of surgeries for pseudoarthrosis, implant failure, infection and elective removal of the implant.Ethics and dissemination Study approved by the institutional ethics committee (number 34249120.9.0000.5505—V.3). The results will be disseminated by publications in peer-reviewed journals and presentations in medical meetings.Trial registration number RBR-3czz68)/UTN U1111-1257-8953.